DAMPAK KEDISIPLINAN BELAJAR TERHADAP PRESTASI BELAJAR MATA KULIAH PAI TARUNA PENERBANG ANGKATAN 67 A,B,C dan 68 A,B SEKOLAH TINGGI PENERBANGAN INDONESIA - Alwazir Abdusshomad (Politeknik Penerbangan Indonesia Curug, 2017)
The aims of this research are (1) to know the discipline in learning PAI subject of aviators cadets period 67 A, B, C and 68 A, B STPI Curug, (2) to know the achievement in PAI subject of aviators cadets period 67 A, B, C and 68 A, B STPI Curug, and (3) to know the effect of the discipline in learning toward the achievement in PAI subject of aviators cadets period 67 A, B, C and 68 A, B STPI Curug. The results of this research are as follows (1) the discipline in learning PAI subject of aviators cadets period 67 A, B, C and 68 A, B STPI Curug is good average. The average score for the questionnaire is 53 that are in the interval score 52 – 63. (2) The achievement in PAI subject of aviators cadets period 67 A, B, C and 68 A, B STPI Curug is good which are 70.45 as the average test score. The score show that it is in the interval score 70 – 79. (3) There is significant impact of the discipline in learning toward the achievement in PAI subject of aviators cadets period 67 A, B, C and 68 A, B STPI Curug. This research uses regression statistic analysis to prove. In this case, the Freg is 9.09, then it is compared to Ftable with df = 1:29 for the significance level 1% = 7.60 and for the significance level 5% = 4.18. It means Freg > Ftable.